Rethinking the senses and their interactions: the case for sensory pluralism - Fulkerson, Matthew (Frontiers in Psychology, 2014)
I argue for sensory pluralism. This is the view that there are many forms of sensory interaction and unity, and no single category that classifies them all. In other words, sensory interactions do not form a single natural kind. This view suggests that how we classify sensory systems (and the experiences they generate) partly depends on our explanatory purposes. I begin with a detailed discussion of the issue as it arises for our understanding of thermal perception, followed by a general account and defense of sensory pluralism.